2020
DOI: 10.1186/s12864-019-6441-3
|View full text |Cite
|
Sign up to set email alerts
|

SMRT sequencing of a full-length transcriptome reveals transcript variants involved in C18 unsaturated fatty acid biosynthesis and metabolism pathways at chilling temperature in Pennisetum giganteum

Abstract: Background: Pennisetum giganteum, an abundant, fast-growing perennial C 4 grass that belongs to the genus Pennisetum, family Poaceae, has been developed as a source of biomass for mushroom cultivation and production, as a source of forage for cattle and sheep, and as a tool to remedy soil erosion. However, having a chilling-sensitive nature, P. giganteum seedlings need to be protected while overwintering in most temperate climate regions. Results:To elucidate the cold stress responses of P. giganteum, we carri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…We uncovered differences in flavonoid metabolism, unsaturated fatty metabolism and TCA cycle between KL and RB under the no-freezing condition (0 h at −25°C). Flavonoid metabolites, acting as antioxidants to remove ROS, can increase FT ( Li et al, 2019 ), while unsaturated fatty metabolism, by enhancing the cell membrane fluidity, can increase plant resistance to cold ( Li et al, 2020 ). The TCA cycle represents energy metabolism, while energy metabolism meant that plant dormancy was weak ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We uncovered differences in flavonoid metabolism, unsaturated fatty metabolism and TCA cycle between KL and RB under the no-freezing condition (0 h at −25°C). Flavonoid metabolites, acting as antioxidants to remove ROS, can increase FT ( Li et al, 2019 ), while unsaturated fatty metabolism, by enhancing the cell membrane fluidity, can increase plant resistance to cold ( Li et al, 2020 ). The TCA cycle represents energy metabolism, while energy metabolism meant that plant dormancy was weak ( Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Both genotypes were cold acclimated to a maximum FT through the natural cooling of the field during the winter before treating them at −25 • C. We uncovered differences in flavonoid metabolism, unsaturated fatty metabolism and TCA cycle between KL and RB under the no-freezing condition (0 h at −25 • C). Flavonoid metabolites, acting as antioxidants to remove ROS, can increase FT (Li et al, 2019), while unsaturated fatty metabolism, by enhancing the cell membrane fluidity, can increase plant resistance to cold (Li et al, 2020).…”
Section: Roles Of Different Metabolism In the Kiwifruit Plant Response To Cold Stressmentioning
confidence: 99%
“…Temperature-dependent alternative splicing might therefore function as a "thermometer" in plants to measure changes in ambient temperature [16,23,25,27]. In Arabidopsis, tea plants and Jujuncao, RT-PCR and RNA sequence analyses revealed that alternative splicing of a variety of genes is changed dramatically during cold acclimation [100][101][102][103]. The findings suggest that alternative splicing events play an important regulatory role in response to cold stress [100][101][102][103][104].…”
Section: Othersmentioning
confidence: 99%
“…With the continuous upgrading and application of sequencing technologies, transcript reconstruction and annotation based on full-length transcript sequencing, followed by mining gene function at the molecular level, have gradually become research hotspots for species with no or difficult-to-assemble reference genomes, e.g., Cistanche tubulosa [ 23 ], Panax japonicus [ 24 ], Cinnamomum porrectum [ 25 ], Pennisetum giganteum [ 26 ], Portulaca oleracea [ 27 ], Nitraria sibirica Pall [ 28 ]. We conducted the first systematic full-length transcriptome analysis of the above-ground tissues of swamp reeds and dune reeds, revealing the alternative splicing pattern of low complexity in long-term adaptation to complex desert adversity.…”
Section: Introductionmentioning
confidence: 99%